Tobin's Q dan Determinannya: Studi Empiris - Averio, Thomas; Kontesa, Maria; Satrio, Arif Budi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze factors that influence firm value, including profitability, leverage, liquidity and firm size. Research on 56 Primary Consumer Goods Sector Companies in Indonesia with an observation period of 2017 to 2021. Data analysis carried out using multiple linear regression shows that profitability has a positive effect while leverage has a negative effect on firm value. This research fails to prove the role of liquidity and company size in explaining changes in firm value.